SIKLUS HIDUP PERUSAHAAN DAN PENGHINDARAN PAJAK - Sandy, Sari Awlia (UNIB Press, 2019)
This study aims to provide empirical evidence that there are differences in tax avoidance that occurs in every corporate life cycle and the life cycle of the company affect tax avoidance. The population in this study are all non-financial companies listed in Indonesia Stock Exchange 2011-2016. The sample of this research is 228 non-financial sector companies listed in Indonesia Stock Exchange 2011-2016. Collection method usig purposive sampling technique. Were selected as a sample of the total 1102 observations this study. The method of analysis in this study using different test Independent Sample t-test and logistic regression analysis.The results of this study indicate that: 1) There is no difference in tax avoidance that occurs in every corporate life cycle either by using ETR proxy or CETR proxy. 2) The life cycle of the company has no effect on tax evasion by the company either by looking at ETR or CETR and doesn’t form a U-Shaped linear pattern.